Electrocardiographic evaluation of the degree of sedation and the isolated use of methadone in healthy dogs - Menegheti, Thais M. [UNESP]; Wagatsuma, Juliana T. [UNESP]; Pacheco, Acacio D. [UNESP]; Perez, Beatriz [UNESP]; Pacheco, Cynara M.; Abimussi, Caio J. X. [UNESP]; Santos, Paulo P. S. dos [UNESP]; Souza Oliva, Valeria N. L. de [UNESP] (Wiley-Blackwell, 2014)
Objective: The present study aimed to investigate the influence of methadone on cardiorespiratory parameters, electrocardiogram and clinical sedation in dogs. Further possible side effects are reported.Study designProspective experimental cross-over study.DogsEight, 1-4-year-old, various breeds of dogs of both genders weighing 9-36kg.MethodsEach dog was treated three times: methadone 0.3mgkg(-1) (M0.3), 0.5mgkg(-1) (M0.5) and 1.0mgkg(-1) (M1.0) intramuscularly. Respiratory rate, heart rate and arterial blood pressure were recorded as well as electrocardiographic evaluation of lead II. Clinical sedation in each treatment received a score (0-3) after drug administration and at 30minute intervals until scores and measurements returned to baseline values.ResultsA significant decrease in heart rate was seen with each dose of methadone and bradycardia (HR<60bpm) was noted in a few dogs at each dose. A clinically significant arrhythmia occurred in one dog at 1mgkg(-1) that required reversal with butorphanol. There was no significant difference in SAP, MAP and DAP between treatments. Some side effects such as salivation, defecation, vocalization and panting, after administration of methadone were observed. There were no differences in mean values of heart rate, P-wave and QRS complex duration and QT interval between treatments.Conclusion and clinical relevanceMethadone administration was associated with panting and a decrease in heart rate at all doses tested in this study. The cardiac rhythm should be monitored carefully in dogs when methadone is administered on its own, especially at higher doses.
Keywords: cardiac arrhythmias; dog; intramuscular; opioid